The Political Economy of Poverty Reduction: A Comparative Study of Two Chinese Provinces - DONALDSON, John A. (Institutional Knowledge at Singapore Management University, 2006)
Is growth good for the poor? In theory, yes. As one influential report on China’s “War on Poverty” suggested, ”Obviously robust economic growth helps reduce poverty, as long as the gains are reasonably distributed” (Rozelle et al. 2000). In practice as well, growth is often a crucial ingredient in the poverty reduction recipe. While this relationship is well founded, important exceptions present themselves – some areas grow, but poverty persists; the economies of other areas remain apparently stagnant, yet poverty diminishes. These exceptions, if studied, will not only illuminate further the causal relationship between these two concepts, but also provide hope for areas for which few prospects of growth exist. This paper examines two neighboring poor Chinese provinces, which faced similar challenges and shared similar characteristics. One grew sluggishly, but the rural poor experienced striking improvement; the other grew rapidly, but its poor people saw few gains, a pattern that can be seen between at least 1991 to the present.